Iron status in cyclists during high-intensity interval training and recovery - Wilkinson, J. G.; Martin, D. T.; Adams, A. A.; Liebman, M. (International Journal of Sports Medicine, 2002)
The purpose of this study was to examine the effects of a 6 week high-intensity interval training (HIT) program, followed by 2 weeks recovery, on iron status in cyclists. Eleven male collegiate cyclists (21.8 +/- 0.8 yr, 71.4 +/- 2.2 kg, and 8.6 +/- 0.9 % body fat) participated in a 6 week cycle training program that consisted of 5 days of high intensity interval and endurance training per week. Hematocrit (Hct), hemoglobin (Hb), red blood cell (RBC) count, serum iron, serum ferritin, and total iron binding capacity (TIBC) were analyzed from venous blood samples taken at baseline (B), and each week following interval training (T1-T6) and recovery (R1-R2). Dietary intakes including iron were monitored weekly. The dependent variables were analyzed by repeated measures ANOVA (p < 0.05). RBC count, Hb and Hct were significantly decreased compared to baseline at T3. Serum iron did not change significantly. Serum ferritin decreased significantly from 55.9 +/- 9.7 at B to 42.2 +/- 8.0 ng x ml -1 at T5 and remained depressed at T6, R1 and R2. TIBC was significantly increased above baseline at T3, T4, T6, R1 and R2. These results suggest that 6 weeks of high-intensity interval training can reduce iron stores. It is possible that this reduction in iron stores over time could adversely affect aerobic cycling performance.